Penerapan Cat dalam Mengukur Tingkat Kesiapan Siswa SMK dalam Menghadapi Ujian Masuk Perguruan Tinggi - Aulia Fitrul Hadi; Deval Gusrion; Harkamsyah Andrianof; Okta Andrica Putra (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2020)
Technology is one of the developments in education in the world, including in utilizing technology in the world of education. Senior high school national exams and their equivalents make use of technology in their implementation. however, the use of technology has not been mastered by students in Indonesia. it is necessary to carry out a simulation in facing the national exam. This community service provides facilities for partners in conducting trials to take the national exam. multimedia applications provide an interactive effect between students and computers. which makes it easier for students to understand the meaning of the questions given on the exam.